2012
DOI: 10.1016/j.actatropica.2011.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Progress towards understanding the ecology and epidemiology of malaria in the western Kenya highlands: Opportunities and challenges for control under climate change risk

Abstract: Following severe malaria epidemics in the western Kenya highlands after the late 1980s it became imperative to undertake eco-epidemiological assessments of the disease and determine its drivers, spatial-temporal distribution and control strategies. Extensive research has indicated that the major biophysical drivers of the disease are climate change and variability, terrain, topography, hydrology and immunity. Vector distribution is focalized at valley bottoms and abundance is closely related with drainage effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 65 publications
0
47
0
Order By: Relevance
“…Dobson, 1989;Staedke et al, 2003;Ernst et al, 2009). In the western Kenya highlands, anopheline larval habitats are generally restricted to the valley bottoms, especially during the dry season (Minakawa et al, 2005b;Mushinzimana et al, 2006;Githeko et al, 2012). Githeko et al (2006) classified study villages as 'valley-bottom', 'mid-hill' and 'hill-top' and found that vector density, EIR and malaria prevalence all decreased upslope.…”
Section: Topographically-driven Surface Saturationmentioning
confidence: 97%
“…Dobson, 1989;Staedke et al, 2003;Ernst et al, 2009). In the western Kenya highlands, anopheline larval habitats are generally restricted to the valley bottoms, especially during the dry season (Minakawa et al, 2005b;Mushinzimana et al, 2006;Githeko et al, 2012). Githeko et al (2006) classified study villages as 'valley-bottom', 'mid-hill' and 'hill-top' and found that vector density, EIR and malaria prevalence all decreased upslope.…”
Section: Topographically-driven Surface Saturationmentioning
confidence: 97%
“…Whereas malaria transmission declined significantly it continued to occur at an unacceptable level with the A. arabiensis predominating transmission. Similarly, the proportion of A. arabiensis in western Kenya highlands has been increasing from nil to about 20% since 2005 (Githeko et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The increase of malaria with household size is realistic in the study area because if a household contains many individuals, when one of them is infected, he could serve as a reservoir for other (Mboera et al, 2014;Nagasaki University, 2007;Ngom & Siegmund, 2010). In general, more people in the study area are low income population and large families with bad quality houses and are therefore prone to malaria (Githeko et al, 2012;Nagasaki University, 2007).…”
Section: Demographic Variables and Malaria Infectionmentioning
confidence: 99%